Inhibition studies of Brucella suis β-carbonic anhydrases with a series of 4-substituted pyridine-3-sulphonamides - Simona Maria Monti; Angela Meccariello; Mariangela Ceruso; Krzysztof Szafrański; Jarosław Sławiński; Claudiu T. Supuran (Taylor & Francis Group, 2018)
The two β-carbonic anhydrases (CAs, EC 4.2.1.1) from the pathogenic bacterium Brucella suis, BsuCA1 and BsuCA2, were investigated for their inhibition profile with a series of pyridine-3-sulphonamide derivatives incorporating 4-hetaryl moieties. BsuCA1 was effectively inhibited by these sulphonamides with inhibition constants ranging between 34 and 624 nM. BsuCA2 was less sensitive to these inhibitors, with KIs in the range of 62 nM - > 10 µM. The nature of the 4-substituent present on the pyridine ring was the main factor influencing the inhibitory profile against both isoforms, with 4-halogenophenylpiperazin-1-yl and 3,4,5-trisubstituted-pyrazol-1-yl derivatives showing the most effective inhibition. Some of these sulphonamides were most effective bacterial CA than human (h) CA I and II inhibitors, making them selective for the prokaryotic enzymes. Investigation of bacterial CA inhibitors may be relevant for finding antibiotics with a new mechanism of action compared to the clinically used agents for which substantial drug resistance emerged.